Purification and Functional Characterization of the Chloroform/Methanol-Soluble Protein 3 (CM3) From Triticum aestivum in Drosophila melanogaster - Thiel, Anna-Lena; Ragab, Mohab; Wagner, Anika E.; Divanovic, Senad; Derer, Stefanie; Sina, Christian (Frontiers in Nutrition, 2020)
Non-celiac wheat sensitivity (NCWS) has been proposed to be an independent disease entity that is characterized by intestinal (e.g. abdominal pain, flatulence) and extra-intestinal symptoms (e.g. headache, fatigue), which are propagated following the ingestion of wheat products. Increased activity of amylase trypsin inhibitors (ATIs) in modern wheat is suggested to be major trigger of NCWS, while underlying mechanisms still remain elusive. Here, we aimed to generate and functionally characterize the most abundant ATI in modern wheat, chloroform/methanol-soluble protein 3 (CM3), in vitro and in Drosophila melanogaster. We demonstrate that CM3 displays α-glucosidase but not α-amylase or trypsin inhibitory activity in vitro. Moreover, fruit flies fed a sucrose-containing diet together with CM3 displayed significant overgrowth of intestinal bacteria in a sucrose-dependent manner while the consumption of α-amylase and α-glucosidase inhibitors was sufficient to limit bacterial quantities in the intestine. Notably, Both CM3 and acarbose-treated flies showed a reduced lifespan. However, this effect was absent in amylase inhibitor (AI) treated flies. Together, given α-glucosidase is a crucial requirement for disaccharide digestion, we suggest that inhibition of α-glucosidase by CM3 enhances disaccharide load in the distal gastrointestinal tract, thereby promoting intestinal bacteria overgrowth. However, it remains speculative if this here described former unknown function of CM3 might contribute to the development of gastrointestinal symptoms observed in NCWS patients which are very similar to symptoms of patients with small intestinal bacterial overgrowth.